Polycaprolactone and Poly-Β-Cyclodextrin Polymer Blend: A Biopolymers Composite Film for Drug Release - Garcia-Herrera, C; Sanchez-Poblete, J; Zapata-Ramirez, P (Springer Science and Business Media B.V., 2022)
Nowadays, biomedical films containing drug carriers are preferred over conventional ones, since the protection of the injury and the therapy is joined within a single device. In the current work, we prepared polycaprolactone (PCL) composite films with β-cyclodextrin (βCD) or its epichlorohydrin crosslinked polymer (βCDP) as ibuprofen (Ibu) drug carrier. The composite films were prepared at different PCL/additive ratios (2, 5, 10 and 20 wt%). ATR-FTIR spectroscopy and water contact angle (WCA) measurements indicated a scarce presence of the additives on the surface. Cross-section scanning electron micrographs showed the presence of aggregates corresponding to βCD and βCDP in the inner regions of the films. The incorporation of βCD and βCDP into the PCL films did not affect their thermal properties as was determined from differential scanning calorimetry (DSC). PCL-films with 10 wt% of the inclusion complexes Ibu@βCD and Ibu@βCDP were prepared and the release studies were performed. At pH = 7.2, PCL-Ibu@βCDP composite film released 55% of Ibu within the first six hours; eight times the amount released by PCL-Ibu@βCD within the same time interval. A plausible mechanism for ibuprofen release is discussed based on the cross-section SEM micrographs of composite films. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.